PENDEKATAN MODEL KMV MERTON UNTUK PENGUKURAN NILAI RISIKO KREDIT OBLIGASI EXPECTED DEFAULT FREQUENCY (EDF) DILENGKAPI GUI R - Agil Setyo Anggoro; Mustafid Mustafid; Puspita Kartikasari (Jurnal Gaussian, 2023)
Bonds are debt securities from the issuer to bondholders with a promise to pay off the principal and the coupon at maturity. Bond investing can generate income while also posing investment risks. One of the risks connected with bond investing is credit risk, which might manifest as a firm collapsing (default). The KMV Merton model approach is one method of measuring bond credit risk. This Merton KMV model computes the Expected Default Frequency (EDF), which is the likelihood of a firm failing in the following years or years. The data processing system using the Graphical User Interface (GUI) can facilitate the analysis process by implementing the Shiny Package in the R studio program. This research case makes use of up to 48 months of monthly corporate asset data from January 2018 to December 2021. The results obtained the value of Expected Default Frequency (EDF) in each company, namely PT Bank Mandiri Tbk obtained a value of 0% and PT Bank Rakyat Indonesia Tbk obtained a value of 1,406668E-113%. Because PT Bank Rakyat Indonesia Tbk's percentage return is higher than that of PT Bank Mandiri Tbk, investors would be better off investing in bonds at PT Bank Mandiri Tbk.